The P323L substitution in the SARS-CoV-2 polymerase (NSP12) confers a selective advantage during infection - Goldswain, H; Dong, X; Penrice-Randal, R; Alruwaili, M; Shawli, GT; Prince, T; Williamson, MK; Raghwani, J; Randle, N; Jones, B; Donovan-Banfield, I; Salguero, FJ; et al. (BioMed Central, 2023)
Background: The mutational landscape of SARS-CoV-2 varies at the dominant viral genome sequence and minor genomic variant population. During the COVID-19 pandemic, an early substitution in the genome was the D614G change in the spike protein, associated with an increase in transmissibility. Genomes with D614G are accompanied by a P323L substitution in the viral polymerase (NSP12). However, P323L is not thought to be under strong selective pressure.